A new energy vehicle roof evaporating shell surface wear-resistant modification treatment method

CN122913060APending Publication Date: 2026-10-16HEFEI LAIKE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611276474.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-21
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]为了解决上述提出传统工艺大多省略基材活化处理工序,仅依靠简单物理清洁去除表面杂质,塑料基材表面惰性强、表面活性基团数量少,导致后续涂层与基材界面结合能力差,涂层极易出现起皮、脱落、翘边等界面失效问题,无法适配车顶高低温交变的严苛服役工况的问题,本申请提供一种新能源汽车顶蒸壳体表面耐磨改性处理方法

Benefits of technology

[0022] 1. This invention generates a large number of polar active groups on the surface of a plastic substrate using low-vacuum argon-oxygen mixed plasma, significantly improving the surface activity and wettability of the substrate. Then, a silane coupling agent is used to achieve bidirectional chemical bonding between the substrate and the wear-resistant coating, constructing a uniform and dense interfacial transition layer. Compared to existing direct spraying processes without pretreatment or a transition layer, this invention completely eliminates defects such as coating interface porosity, delamination, and peeling, significantly improving coating adhesion and long-term service stability, and is suitable for the complex high and low temperature alternating conditions of a top-mounted steam tank.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122913060A_ABST
    Figure CN122913060A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of automobile part processing, and discloses a new energy automobile top evaporation shell surface wear-resistant modification treatment method, which comprises the following steps: S1, plasma activation pretreatment: the surface of a top evaporation shell base material is subjected to low-temperature plasma treatment, so that active groups are generated on the surface of the base material; and S2, silane coupling agent primer coating: a silane coupling agent solution is coated on the surface of the base material subjected to the plasma treatment. A large number of polar active groups are generated on the surface of the plastic base material through low-vacuum argon-oxygen mixed plasma, so that the surface activity and wettability of the base material are greatly improved; then, bidirectional chemical bonding of the base material and a wear-resistant coating is realized through the silane coupling agent, and a uniform and dense interface transition layer is constructed. Compared with the existing direct spraying process without pretreatment and without a transition layer, the application completely eliminates defects such as coating interface pores, delamination and peeling, significantly improves the coating adhesion and long-term service stability, and is suitable for complex vehicle-mounted working conditions of the top evaporation shell with high and low temperature alternation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of automotive parts processing technology, and in particular to a method for wear-resistant modification treatment of the surface of the top steam shell of a new energy vehicle. Background Technology

[0002] As a core protective component of the vehicle's air conditioning system, the roof-mounted evaporator housing in new energy vehicles is constantly exposed to the complex outdoor environment of the vehicle roof. It endures multiple effects, including wind and sand erosion, friction from external objects, alternating high and low temperature cycles, and humid heat aging. Therefore, the housing surface requires high levels of wear resistance, coating adhesion, and weather resistance. Currently, roof-mounted evaporator housings in new energy vehicles are generally made of ABS resin or glass fiber reinforced PP resin, which offer advantages such as lightweight, good formability, and low cost, and are widely used in various new energy vehicle air conditioning assembly scenarios.

[0003] In existing technologies, surface wear-resistant modification processes for plastic housings mostly employ direct spraying of UV-cured coatings, simple sanding pretreatment, or conventional solvent cleaning pretreatment. These processes are relatively simple and have several technical shortcomings in practical applications. Firstly, traditional processes often omit the substrate activation treatment step, relying solely on simple physical cleaning to remove surface impurities. The plastic substrate surface is highly inert with a low number of surface-active groups, resulting in poor interfacial adhesion between the coating and the substrate. This makes the coating prone to peeling, flaking, and edge lifting, failing to meet the harsh operating conditions of alternating high and low temperatures on vehicle roofs.

[0004] Secondly, existing conventional spraying processes lack a dedicated interface transition structure, with the wear-resistant coating directly adhering to the surface of the inert plastic substrate. This results in poor interfacial compatibility and numerous interfacial porosity defects, significantly reducing the overall density and wear resistance of the coating. Furthermore, traditional wear-resistant coatings often employ a single resin system combined with unmodified nanofillers. The poor compatibility between inorganic nanofillers and the organic resin matrix makes them prone to agglomeration and sedimentation, leading to uneven distribution of wear-resistant components within the coating. This results in insufficient wear resistance in certain areas of the shell, making it susceptible to scratches, wear, and exposure of the substrate after prolonged exposure to wind and sand, causing a rapid decline in protective performance.

[0005] Finally, existing UV-cured wear-resistant coatings generally adopt a single UV instant curing process. The curing process involves rapid temperature rise and intense cross-linking reaction. The solvent inside the coating cannot fully evaporate, which easily leads to molding defects such as pinholes, bubbles, and orange peel. In addition, the residual stress inside the coating after curing is relatively large, which can easily cause cracking, aging instability and other problems during long-term use. This seriously shortens the service life of the top steam shell and cannot meet the wear-resistant protection and weather-resistant use requirements of new energy vehicles for long-term outdoor service. Summary of the Invention

[0006] To address the issues raised above, where traditional processes often omit the substrate activation treatment step and rely solely on simple physical cleaning to remove surface impurities, resulting in poor interfacial bonding between the plastic substrate and the substrate due to its high inertness and low number of surface active groups, leading to easy peeling, flaking, and edge lifting of the coating, and thus failing to meet the harsh service conditions of alternating high and low temperatures on the vehicle roof, this application provides a method for wear-resistant modification of the surface of the roof shell of a new energy vehicle.

[0007] The method for wear-resistant modification of the surface of the top steam tank shell of a new energy vehicle provided in this application adopts the following technical solution:

[0008] A method for wear-resistant modification treatment of the surface of the roof steamer shell of a new energy vehicle includes the following steps:

[0009] S1. Plasma activation pretreatment: The surface of the top steam shell substrate is subjected to low-temperature plasma treatment to generate active groups on the substrate surface.

[0010] S2, Silane Coupling Agent Primer: A silane coupling agent solution is applied to the plasma-treated substrate surface to form a chemically bonded transition layer;

[0011] S3, Nanocomposite wear-resistant coating application: A nanoparticle-reinforced UV-cured acrylate composite coating is applied to the surface of the transition layer;

[0012] S4. Gradient curing treatment: Low-temperature pre-curing, ultraviolet light main curing and thermal post-curing are performed in sequence to obtain a wear-resistant modified top steam shell.

[0013] Preferably, in step S1, the low-temperature plasma treatment uses a mixed gas discharge of argon and oxygen, with a treatment power of 80-150W, a treatment time of 30-120s, a gas flow rate of 20-50sccm, and a vacuum degree of 20-50Pa.

[0014] Preferably, in step S2, the silane coupling agent is γ-aminopropyltriethoxysilane, the concentration of the silane coupling agent solution is 1% to 5%, and the solvent is an ethanol-water solution with a volume ratio of 1:1; the coating method is spraying or dipping, and after coating, it is dried at 60 to 80°C for 10 to 20 minutes.

[0015] Preferably, in step S3, the nanocomposite wear-resistant coating comprises, by weight: 30-50 parts of polyurethane acrylate, 20-30 parts of epoxy acrylate, 10-20 parts of trimethylolpropane triacrylate, 2-5 parts of photoinitiator, 5-15 parts of nano wear-resistant filler, 0.5-2 parts of leveling agent, and 0.3-1 parts of defoamer.

[0016] Preferably, the nano-wear-resistant filler is a mixture of nano-silica and nano-alumina in a mass ratio of 2:1 to 3:1, the average particle size of the nano-wear-resistant filler is 15 to 30 nm, and the surface of the nanoparticles is modified by a silane coupling agent.

[0017] Preferably, in step S4, the low-temperature pre-curing temperature is 40–60°C, and the pre-curing time is 5–10 min; the ultraviolet light main curing uses an ultraviolet lamp with a wavelength of 365 nm, an irradiation intensity of 800–1200 mJ / cm², and a main curing time of 10–30 s; the thermal post-curing temperature is 80–100°C, and the thermal post-curing time is 20–40 min.

[0018] Preferably, the substrate of the top steaming shell is ABS resin or glass fiber reinforced PP resin, and the dry film thickness of the nanocomposite wear-resistant coating is 15-25 μm.

[0019] Preferably, the silane coupling agent used for the surface modification of the nanoparticles is γ-methacryloyloxypropyltrimethoxysilane, the modification temperature is 50-70°C, and the modification time is 30-60 min.

[0020] Preferably, the photoinitiator is either 1173 photoinitiator or 184 photoinitiator, the leveling agent is an organosilicon leveling agent, and the defoamer is a polyether defoamer.

[0021] In summary, this application includes the following beneficial technical effects:

[0022] 1. This invention generates a large number of polar active groups on the surface of a plastic substrate using low-vacuum argon-oxygen mixed plasma, significantly improving the surface activity and wettability of the substrate. Then, a silane coupling agent is used to achieve bidirectional chemical bonding between the substrate and the wear-resistant coating, constructing a uniform and dense interfacial transition layer. Compared to existing direct spraying processes without pretreatment or a transition layer, this invention completely eliminates defects such as coating interface porosity, delamination, and peeling, significantly improving coating adhesion and long-term service stability, and is suitable for the complex high and low temperature alternating conditions of a top-mounted steam tank.

[0023] 2. This invention modifies nanofillers with silane grafting, solving the problems of easy agglomeration, poor compatibility with resins, and low coating density of traditional nanofillers. Simultaneously, by compounding polyurethane acrylate, epoxy acrylate, and multifunctional monomers, it balances coating toughness, hardness, and crosslinking density. The modified nanoparticles form a uniform, wear-resistant skeleton structure within the coating, significantly improving its friction and scratch resistance, effectively addressing the shortcomings of traditional single-resin coatings such as low hardness, insufficient wear resistance, and short service life.

[0024] 3. This invention achieves step-by-step molding through segmented gradient curing, enabling slow solvent evaporation, rapid photocrosslinking, and deep post-crosslinking. This avoids molding defects such as coating blistering, pinholes, and shrinkage cracks, effectively releasing residual stress within the coating and further improving its density, aging resistance, and dimensional stability. The process parameters of this invention have high matching degree and good repeatability, consistently producing modified top-evapor shells with uniform thickness, excellent adhesion, and outstanding wear resistance and durability, making it highly applicable to industrial production. Attached Figure Description

[0025] Figure 1 This is a flowchart of a method for wear-resistant modification of the surface of the top steam shell of a new energy vehicle. Detailed Implementation

[0026] The following is in conjunction with the appendix Figure 1 This application will be described in further detail.

[0027] This invention provides a method for wear-resistant modification of the surface of a roof steamer shell in new energy vehicles. It is based on plasma activation pretreatment, construction of a silane coupling agent transition layer, application of a nanocomposite wear-resistant coating, and a multi-stage gradient curing coupling process. This method is applicable to wear-resistant modification of the surface of roof steamer shells in new energy vehicles made of ABS resin and glass fiber reinforced PP resin. The process of this invention includes four core steps: plasma activation pretreatment, silane coupling agent primer treatment, nanocomposite wear-resistant coating application, and gradient curing treatment. First, the surface of the shell substrate is activated and modified using low-vacuum mixed gas low-temperature plasma, introducing a large number of active groups to improve the wettability and grafting ability of the substrate surface. Then, a uniform and stable chemically bonded transition layer is constructed on the substrate surface by coating and drying with a silane coupling agent solution of a specific concentration, achieving interfacial compatibility between the inorganic coating and the organic substrate. Subsequently, a UV-curable acrylate composite coating modified and enhanced by nanoparticles is applied, relying on the multi-component resin compound system and modified nanofillers to synergistically improve the coating's density and wear resistance. Finally, a three-stage gradient curing process of low-temperature pre-curing, UV main curing, and thermal post-curing is adopted to gradually complete the coating solvent evaporation, photo-crosslinking curing, and post-crosslinking densification, ultimately obtaining a top-evapor shell modified structure with strong bonding, uniform thickness, and excellent wear resistance.

[0028] In a preferred embodiment, step S1, low-temperature plasma treatment, employs a synergistic discharge of a mixed argon and oxygen gas to activate the substrate surface. The plasma treatment environment is a low-vacuum, sealed cavity. By precisely controlling the discharge power, treatment duration, gas flow rate, and vacuum level, uniform activation of the substrate surface is achieved, avoiding localized over-treatment or inactivation defects. Oxygen in the mixed gas is used to oxidize and generate hydroxyl and carboxyl polar active groups on the substrate surface, while argon is used to stabilize the discharge atmosphere and improve plasma uniformity, ensuring a consistent distribution of active groups across the entire substrate surface and providing uniform reaction sites for the subsequent silane coupling agent grafting reaction.

[0029] In a preferred embodiment, step S2 uses γ-aminopropyltriethoxysilane as an interface coupling modifier. This type of silane coupling agent can bond with the active groups on the substrate surface at one end, and crosslink with the subsequent acrylate coating system at the other end, achieving double-end chemical bonding between the substrate and the coating. Using an ethanol-water mixture as a solvent ensures uniform hydrolysis of the silane coupling agent and prevents its aggregation and precipitation. Spraying or dipping methods can be used to adapt to different shell shapes. Combined with a medium-low temperature drying process, the hydrolyzed groups undergo dehydration condensation, forming a dense, continuous, ultra-thin transition interface layer.

[0030] In a preferred embodiment, the nanocomposite wear-resistant coating in step S3 uses a polyurethane acrylate and epoxy acrylate composite resin system, combined with trimethylolpropane triacrylate reactive diluent monomer, which can effectively adjust the coating viscosity and crosslinking density. The polyurethane acrylate imparts good toughness and adhesion to the coating, the epoxy acrylate enhances the coating hardness and resistance to media, and the trimethylolpropane triacrylate multifunctional monomer significantly improves the UV curing crosslinking efficiency, ensuring rapid coating formation. The accompanying photoinitiator can rapidly generate active free radicals under UV irradiation, initiating the polymerization and crosslinking of the resin system.

[0031] In a preferred embodiment, the nano-wear-resistant filler employs a composite system of nano-silica and nano-alumina. Both nano-fillers have small particle sizes, high hardness, and uniform dispersion, enabling them to form a dense, wear-resistant skeletal structure within the coating. Nano-silica improves coating density and reduces porosity, while nano-alumina significantly enhances surface hardness and abrasion resistance. Simultaneously, surface modification treatment with a silane coupling agent effectively improves the interfacial compatibility between the inorganic nano-filler and the organic resin system, preventing nanoparticle aggregation and sedimentation, and ensuring uniform and stable overall coating performance.

[0032] In a preferred embodiment, the nanoparticle surface modification is performed using γ-methacryloxypropyltrimethoxysilane graft modification. This coupling agent contains acrylate active functional groups, which can copolymerize and crosslink with the coating resin system, transforming the simple physical doping of the nano-wear-resistant filler into chemical graft reinforcement, further improving the overall integrity and wear resistance of the coating. By controlling the modification temperature and modification time, uniform grafting on the nanoparticle surface can be ensured, balancing filler dispersibility and reactivity.

[0033] In a preferred embodiment, the coating additive system uses either 1173 or 184 photoinitiator, both of which have UV response bands compatible with a 365nm UV curing light source, exhibiting high initiation efficiency and low yellowing, making them suitable for surface coating modification of automotive exterior parts. Organosilicon leveling agents effectively reduce coating surface tension, improve coating leveling properties, and eliminate brush marks and orange peel defects; polyether defoamers effectively eliminate microbubbles generated during coating stirring and application, ensuring a dense, pinhole-free coating after curing.

[0034] In a preferred embodiment, step S4 employs a three-stage gradient curing mode: low-temperature pre-curing, UV-curing, and thermal post-curing. Low-temperature pre-curing allows the organic solvent inside the coating to evaporate slowly, avoiding solvent encapsulation, bubbling, and pinhole problems caused by rapid curing, while also allowing the coating to initially set. UV-curing utilizes high-energy UV light to rapidly excite the photoinitiator to decompose, achieving rapid cross-linking and curing of the resin system with high molding efficiency. Thermal post-curing further promotes secondary cross-linking of residual active groups inside the coating, eliminates residual stress inside the coating, and improves the coating's density, adhesion, and thermal stability.

[0035] In a preferred embodiment, the automatic focusing and alignment calibration adopt a closed-loop control method. Before formal coating and curing, the uniformity of coating and the consistency of curing imaging are ensured by the equipment sensing components in conjunction with the whole machine debugging. This ensures that the final nanocomposite wear-resistant coating dry film thickness is stably controlled at 15-25μm, with small coating thickness uniformity error, which can meet the appearance and protection performance requirements of the top steam shell of new energy vehicles.

[0036] To further illustrate the feasibility of the process of the present invention, the process parameters of the present invention will be described in detail below with reference to three specific embodiments.

[0037] Example 1:

[0038] This embodiment uses an ABS resin top steaming shell, and the specific process steps are as follows:

[0039] S1. Plasma activation pretreatment: Argon and oxygen mixed gas discharge treatment is used, with a treatment power of 80W, a treatment time of 120s, a gas flow rate of 20sccm, and a vacuum degree of 20Pa to complete the activation of the substrate surface.

[0040] S2, Silane Coupling Agent Primer: γ-aminopropyltriethoxysilane is selected, and a 1% ethanol-water solution is prepared. It is then applied by spraying and dried at 60℃ for 20 minutes.

[0041] S3. Nanocomposite wear-resistant coating application: 30 parts by weight of polyurethane acrylate, 20 parts by weight of epoxy acrylate, 10 parts by weight of trimethylolpropane triacrylate, 2 parts by weight of 1173 photoinitiator, 5 parts by weight of nano wear-resistant filler, 0.5 parts by weight of silicone leveling agent, and 0.3 parts by weight of polyether defoamer; the nano filler is a mixture of silica and alumina in a mass ratio of 2:1, with an average particle size of 15nm, modified by γ-methacryloyloxypropyltrimethoxysilane at 50℃ for 60min; the dry film thickness after coating is 15μm.

[0042] S4. Gradient curing treatment: Pre-curing at 40℃ for 10 min, main curing with 800mJ / cm², 365nm ultraviolet light for 30 s, and post-curing at 80℃ for 40 min to complete the modified preparation.

[0043] Example 2:

[0044] This embodiment uses a glass fiber reinforced PP resin top steaming shell, and the specific process steps are as follows:

[0045] S1. Plasma activation pretreatment: processing power 120W, processing time 75s, gas flow rate 35sccm, vacuum degree 35Pa;

[0046] S2, Silane Coupling Agent Primer: Prepare a 3% γ-aminopropyltriethoxysilane ethanol-water solution, dip-coat, and dry at 70℃ for 15 min;

[0047] S3, Nanocomposite wear-resistant coating: 40 parts polyurethane acrylate, 25 parts epoxy acrylate, 15 parts trimethylolpropane triacrylate, 3.5 parts 184 photoinitiator, 10 parts nano wear-resistant filler, 1.2 parts leveling agent, 0.6 parts defoamer; nano filler mass ratio 2.5:1, average particle size 22nm, modified at 60℃ for 45min; dry film thickness 20μm;

[0048] S4. Gradient curing treatment: Pre-curing at 50℃ for 7 minutes, main curing with 1000mJ / cm² UV light for 20 seconds, and post-curing at 90℃ for 30 minutes.

[0049] Example 3:

[0050] This embodiment uses an ABS resin top steaming shell, and the specific process steps are as follows:

[0051] S1. Plasma activation pretreatment: processing power 150W, processing time 30s, gas flow rate 50sccm, vacuum degree 50Pa;

[0052] S2, Silane Coupling Agent Primer: Prepare a 5% concentration of γ-aminopropyltriethoxysilane ethanol-water solution, spray it on, and dry it at 80℃ for 10 min;

[0053] S3, Nanocomposite wear-resistant coating: 50 parts polyurethane acrylate, 30 parts epoxy acrylate, 20 parts trimethylolpropane triacrylate, 5 parts 184 photoinitiator, 15 parts nano wear-resistant filler, 2 parts leveling agent, 1 part defoamer; nano filler mass ratio 3:1, average particle size 30nm, modified at 70℃ for 30min; dry film thickness 25μm.

[0054] S4. Gradient curing treatment: Pre-curing at 60℃ for 5 minutes, main curing with 1200mJ / cm² UV light for 10 seconds, and post-curing at 100℃ for 20 minutes.

[0055] The above three sets of embodiments fully cover the entire range of process parameters defined in the claims of this invention. The process is stable and highly repeatable, and can effectively achieve wear-resistant modification of the surface of the top steam shell of new energy vehicles. Compared with the traditional single spraying and single curing process, this invention significantly improves the coating interface bonding and surface wear resistance stability through the coupled innovation of interface activation, chemical bonding transition, nanocomposite reinforcement and gradient segmented curing.

[0056] The foregoing description, with reference to preferred embodiments, illustrates an exemplary implementation of a method for wear-resistant modification of the surface of a top-mounted steam tank shell for new energy vehicles provided by this disclosure. However, those skilled in the art will understand that various modifications and alterations can be made to the above specific embodiments without departing from the spirit of this disclosure, and various combinations can be made to the various technical features and structures proposed in this disclosure without exceeding the protection scope of this disclosure, which is determined by the appended claims.

Claims

1. A method for wear-resistant modification treatment of the surface of the top steam tank shell of a new energy vehicle, characterized in that, Includes the following steps: S1. Plasma activation pretreatment: The surface of the top steam shell substrate is subjected to low-temperature plasma treatment to generate active groups on the substrate surface. S2, Silane Coupling Agent Primer: A silane coupling agent solution is applied to the plasma-treated substrate surface to form a chemically bonded transition layer; S3, Nanocomposite wear-resistant coating application: A nanoparticle-reinforced UV-cured acrylate composite coating is applied to the surface of the transition layer; S4. Gradient curing treatment: Low-temperature pre-curing, ultraviolet light main curing and thermal post-curing are performed in sequence to obtain a wear-resistant modified top steam shell.

2. The method for wear-resistant modification treatment of the surface of the top steam shell of a new energy vehicle according to claim 1, characterized in that, In step S1, the low-temperature plasma treatment uses a mixed gas discharge of argon and oxygen, with a treatment power of 80-150W, a treatment time of 30-120s, a gas flow rate of 20-50sccm, and a vacuum degree of 20-50Pa.

3. The method for wear-resistant modification treatment of the surface of the top steam shell of a new energy vehicle according to claim 1, characterized in that, In step S2, the silane coupling agent is γ-aminopropyltriethoxysilane, the concentration of the silane coupling agent solution is 1% to 5%, and the solvent is an ethanol-water solution with a volume ratio of 1:

1. The coating method is spraying or dipping, and after coating, it is dried at 60 to 80°C for 10 to 20 minutes.

4. The method for wear-resistant modification treatment of the surface of the top steam shell of a new energy vehicle according to claim 1, characterized in that, In step S3, the nanocomposite wear-resistant coating comprises, by weight: 30-50 parts of polyurethane acrylate, 20-30 parts of epoxy acrylate, 10-20 parts of trimethylolpropane triacrylate, 2-5 parts of photoinitiator, 5-15 parts of nano wear-resistant filler, 0.5-2 parts of leveling agent, and 0.3-1 parts of defoamer.

5. The method for wear-resistant modification treatment of the surface of the top steam shell of a new energy vehicle according to claim 4, characterized in that, The nano-wear-resistant filler is a mixture of nano-silica and nano-alumina in a mass ratio of 2:1 to 3:

1. The average particle size of the nano-wear-resistant filler is 15 to 30 nm, and the surface of the nanoparticles is modified with a silane coupling agent.

6. The method for wear-resistant modification treatment of the surface of the top steam shell of a new energy vehicle according to claim 1, characterized in that, In step S4, the low-temperature pre-curing temperature is 40-60℃, and the pre-curing time is 5-10 min; the ultraviolet light main curing uses an ultraviolet lamp with a wavelength of 365nm, an irradiation intensity of 800-1200mJ / cm², and a main curing time of 10-30s; the thermal post-curing temperature is 80-100℃, and the thermal post-curing time is 20-40 min.

7. The method for wear-resistant modification treatment of the surface of the top steam shell of a new energy vehicle according to claim 1, characterized in that, The substrate of the top steaming shell is ABS resin or glass fiber reinforced PP resin, and the dry film thickness of the nanocomposite wear-resistant coating is 15-25 μm.

8. The method for wear-resistant modification treatment of the surface of the top steam shell of a new energy vehicle according to claim 5, characterized in that, The silane coupling agent used for the surface modification of the nanoparticles is γ-methacryloyloxypropyltrimethoxysilane, the modification temperature is 50-70℃, and the modification time is 30-60 min.

9. The method for wear-resistant modification treatment of the surface of the top steam shell of a new energy vehicle according to claim 4, characterized in that, The photoinitiator is either 1173 photoinitiator or 184 photoinitiator, the leveling agent is an organosilicon leveling agent, and the defoamer is a polyether defoamer.